Pro-resolving and pro-inflammatory fatty acid-derived mediators in sputum of stable state bronchiectasis patients - Terranova, Leonardo; Risé, Patrizia; Gramegna, Andrea; Pinna, Christian; Agostoni, Carlo; Syrén, Marie-Louise; Turolo, Stefano; Marchisio, Paola; Amati, Francesco; Aliberti, Stefano; Sala, Angelo; Blasi, Francesco (Respiratory research, 2022)
Background Bronchiectasis is characterized by neutrophilic inflammation and frequent exacerbations often associated with infections. Lipid mediators play critical roles in the inflammatory response, and the balance between anti-inflammatory and pro-inflammatory mediators could drive to chronic inflammation. The aim of this study was to evaluate the metabolites of docosahexaenoic acid and arachidonic acid in sputum of adults with bronchiectasis defining their associations with clinical data, bacterial load and neutrophil elastase. Methods An observational, cross-sectional study was conducted at the bronchiectasis program of the Policlinico Hospital in Milan, Italy, where patients were enrolled. Active neutrophil elastase was measured by enzyme-linked immunosorbent assay, pro-resolving and pro-inflammatory fatty acid-derived mediators were evaluated by mass spectrometry and respiratory pathogens were assessed by real-time PCR. Analysis were performed on sputum collected during stable state and clinical data were also collected. Results Levels of pro-inflammatory mediators derived from arachidonic acid metabolism showed association with neutrophil elastase, were proportional to Pseudomonas aeruginosa identifications and were linked with radiological gravity index, while the concentrations of pro-resolution mediators derived from docosahexaenoic acid were associated with a better health status, highlighted by the inverse correlation with radiological gravity index, bacterial infections and sputum volume production. Conclusion Pro-inflammatory mediators derived from FA metabolisms are associated with severity of bronchiectasis while DHA-derived metabolites are inversely associated with severity of the disease, which may be used for personized treatment of bronchiectasis.